Analisa Kualitas Layanan Aplikasi Mobile Banking pada Nasabah Bjb Cabang Tangerang Menggunakan Metode Servqual - Ageng Agti Prihatiningrum; Eva Zuraidah (Journal of Information System Research (JOSH), 2022)
Service quality is an important factor in competitive advantage in a company. The importance of service quality can help companies differentiate themselves from other companies. It can be seen that in the BJB bank mobile banking application service, there are still complaints and customer dissatisfaction, because there is still frequent maintenance on the BJB Mobile application, causing customer transactions to be disrupted and transaction failures. In addition to this, during the complaint process when a failed transaction occurs, the response given by the Bank must go through a lengthy process. The purpose of this study was to measure the quality of service that affects the level of customer satisfaction with the servqual method. Measurement of patient satisfaction was done by looking for samples with the Slovin method and obtained 98 respondents. Measurement of the level of customer satisfaction on the 5 dimensions of service quality of service, namely tangible, reliability, responsiveness, assurance, and empathy, and the average result of the gap between reality and customer expectations is -0.10. The gaps are grouped based on attributes using an IPA (Importance Performance Analysis) diagram with Tangible dimension results with a gap value of -0.11, Reliability with a gap value of -0.02, Responsiveness with a gap value of -0.06, Assurance with a gap of -0.01, and Empathy with a gap value of -0.31.